Debate on the Appropriate Methods for Conducting Impact Evaluation of Programs within the Development Context - Enyonam B. Norgbey (Journal of MultiDisciplinary Evaluation)
Background: Donors and decision-makers use impact evaluation reports to assess the effectiveness of development programs and identify ways to improve the design and implementation of projects, programs, and policies in developing countries.